Three States of Wax - Parra Cancino, Juan; Ircam Forum: 30 years IRCAM, Paris, France March 19-22. 2024 (2024)
guitar, trumpet, and electronics.
Lecture performance of Three States of Wax (Juan Parra Cancino, guitar + electronics & Jonathan Impett, trumpet + electronics)
FRIS
Editorial review
Keywords: Music, Thought and Technology